Do Intellectual Capital and Environmental, Social, and Governance (ESG) on Financial Performance? - Fathonah, Andina Nur; Ali, Muhammad; Apriliana, Tria (Universitas Batanghari Jambi, 2024)
The majority of Indonesians depend on agriculture as an important sector. PSAK 69 regarding agriculture must be supported by companies engaged in this field because they must have rules for preparing Financial Statements. This study aims to determine the effect of Intellectual Capital and ESG on Financial Performance (Agriculture Sector 2019-2021 Period). In the context of IC, the dependent variable discussed in this study is symbolized by VAIC in three ways: Value Added Capital Cefficient (VACA), Human Capital Cefficient (VAHU), and Structural Capital Cefficient (STVA). In addition, there is an additional dependent variable, ESG. Financial performance, represented by Return on Asset (ROA), is the independent variable of this study. This study is quantitative. The Indonesia Stock Exchange Annual Report is the source of secondary time series data used in this study. The study will take 36 samples, with 12 companies selected to be sampled for three years. This study uses the explanatory method. This study uses descriptive analysis and multiple linear regression to analyze the data. Only VAHU affects ROA, while the other variables do not. Together, VACA, VAHU, STVA, and ESG have an influence of 60.97% on ROA, and other variables not examined in this study have an influence of 39.03%.